Mapping the Landscape of Brand Equity Research: A Bibliometric Analysis of SCOPUS Data (1993-2023) - Chuan Zheng; Munirah Khamarudin; Azanin Ahmad (International Review of Management and Marketing)
This study aims to conduct a comprehensive bibliometric analysis of brand equity research from 1993 to 2023, focusing on identifying influential publications, authors, journals, theoretical models, thematic evolution, and potential research gaps. The research employs a rigorous methodology, initially analyzing 1,483 articles from 449 sources from the SCOPUS database. Various analytical techniques by VOSviewer and Biblioshiny, including source, author, document, thematic, and keyword analysis, are utilized to extract insights. Key findings include the identification of influential publications, authors, and journals, as well as the categorization and models of brand equity. Additionally, prominent theoretical models are highlighted, alongside emerging topics and research clusters. This study provides valuable insights for researchers, practitioners, and policymakers in understanding the foundational elements and contemporary trends in brand equity research. This research contributes to the literature by offering a comprehensive and up-to-date analysis of brand equity research, highlighting existing knowledge gaps and potential avenues for future investigation.